Canada's implementation of the Paragraph 6 Decision: is it sustainable public policy? - Cosio Andre; Esmail Laura C; Cohen-Kohler Jillian C (BMC, 2007)
Abstract Background Following the Implementation of Paragraph 6 of the Doha Declaration on TRIPS and Public Health, Canada was among the first countries globally to amend its patent law, which resulted in Canada's Access to Medicines Regime (CAMR). CAMR allows the production and export of generic drugs to developing countries without the requisite manufacturing capacity to undertake a domestic compulsory license. CAMR has been the subject of much criticism lodged at its inability to ensure fast access to urgent medicines for least developing and developing countries in need. Only recently did the Canadian government grant Apotex the compulsory licenses required under CAMR to produce and export antiretroviral therapy to Rwanda's population. Methods The objective of this research is to investigate whether the CAMR can feasibly achieve its humanitarian objectives given the political interests embedded in the crafting of the legislation. We used a political economy framework to analyze the effect of varied institutions, political processes, and economic interests on public policy outcomes. In-depth, semi-structured interviews were conducted with nineteen key stakeholders from government, civil society and industry. Qualitative data analysis was performed using open-coding for themes, analyzing by stakeholder group. Results CAMR is removed from the realities of developing countries and the pharmaceutical market. The legislation needs to include commercial incentives to galvanize the generic drug industry to make use of this legislation. CAMR assumes that developing country governments have the requisite knowledge and human resource capacity to make use of the regime, which is not the case. The legislation does not offer sufficient incentives for countries to turn to Canada when needed drugs may be procured cheaply from countries such as India. In the long term, developing and least developing countries seek sustainable solutions to meet the health needs of their population, including developing their own capacity and local industries. Conclusion CAMR is symbolically meaningful but in practice, limited. The Rwanda case will be noteworthy in terms of the future of the legislation. To meet its intended international health objectives, this legislation needs to be better informed of developing country needs and global pharmaceutical market imperatives. Finally, we contend that serious public policy change cannot strike a balance between all vested interests. Above all, any feasible policy that aims to facilitate compulsory licensing must prioritize public health over trade or economic interests.